Is there a relationship between inflammation and depression in athletes? - Ostapiuk-Karolczuk, J.; Kasperska, A.; Botwina, R. (Trends in Sport Sciences, 2015)
Overtraining is a maladaptive state of athlete`s body related to the physical, behavioral and emotional condition, occurring when exercise training exceeds the recoverability. The cytokine hypothesis of overtraining promoted in recent years is seen as the prevailing theory explaining the understanding of the overtraining phenomenon. The high level of pro-inflammatory cytokines (IL-6, TNFá, IL-1â) involved in the inflammatory response may strongly influence not only the central nervous system but also the endocrine and immune systems. Moreover, there is a range of factors in athlete`s life that appear to increase the risk of depression development, such as psychological and emotional stress associated with sports competition. The aim of this review was to reveal the role of hig h level of proinflammatory cytokines observed in OTS with the possible occurrence of depression symptoms in athletes. Latest findings have shown an important role of the same pro-inflammatory cytokines in the development of depression. The study discusses a potential mechanism responsible for the development of depression in athletes, which may be helpful in the quick diagnosis of depression basis in athletes. Due to the low number of studies concerning depression and inflammation in athletes further research should be conducted.